Türkiye’de para ikamesi süreci ve hiperenflasyonist dinamikler: ekonometrik bir analiz - TUNAY, KAŞİF BATU (My University, 2022)
Türkiye uzun bir fiyat istikrarı sürecinin ardından yeniden enflasyonist baskılar yaşamaya başlamıştır. 2017 sonrasında giderek artan enflasyon oranları nedeniyle para ikamesi süreci hız kazanmıştır. Son dönemde yaşanan kur şokları ulusal paradan kaçışı artırmış, ekonomik birimlerin hem yabancı paraya hem de tüketime yönelik talepleri yükselmiştir. Söz konusu gelişmeler, güçlenen enflasyonist baskıların bir hiperenflasyona evrilme olasılığının sorgulanmasına yol açmıştır. Bu bağlamda çalışmanın amacı, Türkiye’de hiperenflasyonist dinamiklerin ekonometrik olarak analiz edilmesidir. Moosa’nın (2000) 1920’lerdeki Alman hiperenflasyonunu analiz etmek için geliştirdiği model Türkiye’ye uyarlanmıştır. Türkiye için yapılan parametre tahminleri, orijinal modelinkilerle karşılaştırılmış ve ulusal paranın değer ölçme ve saklama işlevlerinin zayıfladığı belirlenmiştir. Para arzındaki değişimin kurlar üzerinde güçlü bir etkisi olduğu da görülmüştür. Bu bulgular, para politikalarının etkinliğinin düştüğünü ve enflasyonistsürecin daha da şiddetlenebileceğini göstermektedir.

After a long period of price stability, Turkey has started to experience inflationary pressures again. Due to the increasing inflation rates after 2017, the currency substitution process accelerated. The exchange rate shocks experienced in the recent period has accelerated the flight from the national currency, and the demands of economic units for both foreign currency and consumption have increased. These developments led to the questioning of the possibility of increasing inflationary pressures to evolve into hyperinflation. In this context, the aim of the study is to econometrically analyze the hyperinflationary dynamics in Turkey. The model developed by Moosa (2000) to analyze the German hyperinflation in the 1920s was adapted for Turkey. The parameter estimates obtained for Turkey were compared with those of the original model and it was determined that the value measurement and storage functions of the national currency weakened. It has also been observed that the change in money supply has a strong effect on exchange rates. These findings show that the effectiveness of monetary policies has decreased and the inflationary process may become stronger.
Keywords: : Currency Substitution; Hyperinflation; Currency Shocks; State-space Models; Para İkamesi; Hiperenflasyon; Kur Şokları; Durum-uzay Modelleri